Supplementry Effect Of Biofertilizers In Dendrobium - Binisha S (Department of Pomology and Floriculture, College of Horticulture, 2003)
Studies on "Supplementary effect of biofertilizers in Dendrobium" were carried out in the orchidarium of All India Co-ordinated Floriculture Improvement Project, Department of Pomology and Floriculture, College of Horticulture, Vellanikkara during the period from July 2002 to August 2003. The study was conducted using Dendrobium var. Sonia 17, with the main objective of determinjng the effect of biofertilizers on growth and flowering of Dendrobium in combination with inorganic fertilizers. Results revealed that, different treatments involving combinations of biofertilizers and inorganic fertilizers highly influenced the growth characters of the plant. The plant height obtained was the highest for NPK 10:5:10 along with Azospirillum. This treatment also improved vegetative characters like number of leaves per plant, number of leafy shoots, girth of shoot and internodal length. Maximum number of pseudobulbs was obtained for the treatment receiving NPK 10:5: 1 0 inoculated with Azospirillum and phosphobacteria at the time of planting. Root characters and dry matter production were markedly influenced by biofertilizer treatments. Root length and root number were found to be the highest for the treatment receiving 20: 1 0: 1 0 NPK along with Azospirillum, phosphobacteria and Arbuscular Mycorrhizal Fungi. These three biofertilizers along with 10:5: 10 NPK yielded the highest root volume. Dry matter production at the time of flowering was markedly influenced by biofertilizer application. Treatment receiving 20: 1 0: 1 0 NPK along with Azospirillum and phosphobacteria recorded the highest value for dry matter production. Plants. which were inoculated with Azospirillum at the time of planting and sprayed with 20: 1 0: 1 0 NPK at 0.2 per cent concentration, came to flowering early, produced larger flowers, lengthy spikes and more number of flowers per spike. Number of spikes per plant, colour variation, spike internodal length, pedicel length and longevity of spike on the plant were not found to be influenced by